2019
DOI: 10.1038/s41523-019-0128-4
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and survival among a cohort of breast cancer patients is partially mediated by tumor characteristics

Abstract: Obesity exerts adverse effects on breast cancer survival, but the means have not been fully elucidated. We evaluated obesity as a contributor to breast cancer survival according to tumor molecular subtypes in a population-based case–cohort study using data from the Surveillance Epidemiology and End Results (SEER) program. We determined whether obese women were more likely to be diagnosed with poor prognosis tumor characteristics and quantified the contribution of obesity to survival. Hazard ratios (HRs) and 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 49 publications
3
100
1
Order By: Relevance
“…There is good evidence that obesity is associated with the development of premenopausal triple-negative breast cancer [ 80 ]. In patients with confirmed breast cancers, obesity also increases the risk of metastasis, tumor recurrence, and mortality [ 81 , 82 ].…”
Section: Influence Of Obesity On Breast Cancermentioning
confidence: 99%
“…There is good evidence that obesity is associated with the development of premenopausal triple-negative breast cancer [ 80 ]. In patients with confirmed breast cancers, obesity also increases the risk of metastasis, tumor recurrence, and mortality [ 81 , 82 ].…”
Section: Influence Of Obesity On Breast Cancermentioning
confidence: 99%
“…Although numerous studies have reported a statistical association between obesity and BCRL [ [13] , [14] , [15] , [16] ], [ [13] , [14] , [15] , [16] ] the causal relation and underlying mechanisms remain unclear. Given that studies have reported that obesity increases patients’ risks of larger tumors and axillary lymph node invasion and is considered a negative prognostic factor [ 29 , 30 ], patients with obesity could have received more treatments associated with subsequent occurrence of BCRL. Thus, obesity could in fact be indirectly connected to BCRL.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity increases the risk of several types of cancer, including post-menopausal breast cancer 3 . It is also a poor prognosis marker for several cancers and causes increased death rates [4][5][6] . It is estimated that 14% of cancer deaths in men and 20% in women are related to obesity 5 .…”
Section: Introductionmentioning
confidence: 99%